The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41467-017-00210-6
|View full text |Cite
|
Sign up to set email alerts
|

Two mouse models reveal an actionable PARP1 dependence in aggressive chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) remains an incurable disease. Two recurrent cytogenetic aberrations, namely del(17p), affecting TP53, and del(11q), affecting ATM, are associated with resistance against genotoxic chemotherapy (del17p) and poor outcome (del11q and del17p). Both del(17p) and del(11q) are also associated with inferior outcome to the novel targeted agents, such as the BTK inhibitor ibrutinib. Thus, even in the era of targeted therapies, CLL with alterations in the ATM/p53 pathway remains a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 62 publications
3
53
0
1
Order By: Relevance
“…Thus, it has been speculated that it is the HR defect in BRCA1/2 -mutated cancer cells that confers sensitivity to PARP inhibition [73,74]. In line with this concept, further experiments have shown that PARP inhibition is indeed selectively toxic in cancer cells that harbor aberrations in additional HR genes, such as ATM , RAD51 , RAD54 , DSS1 , RPA1 , NBN , ATR , CHEK1 , CHEK2 , FANCD2 , FANCA and FANCC [77,78,79,80,81]. Given that several critical phenotypes that are associated with BRCA1 or BRCA2 deficiency are also detectable in situations where no germline BRCA1/2 mutation can be detected, the term ‘BRCA-ness' has been coined.…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 57%
See 3 more Smart Citations
“…Thus, it has been speculated that it is the HR defect in BRCA1/2 -mutated cancer cells that confers sensitivity to PARP inhibition [73,74]. In line with this concept, further experiments have shown that PARP inhibition is indeed selectively toxic in cancer cells that harbor aberrations in additional HR genes, such as ATM , RAD51 , RAD54 , DSS1 , RPA1 , NBN , ATR , CHEK1 , CHEK2 , FANCD2 , FANCA and FANCC [77,78,79,80,81]. Given that several critical phenotypes that are associated with BRCA1 or BRCA2 deficiency are also detectable in situations where no germline BRCA1/2 mutation can be detected, the term ‘BRCA-ness' has been coined.…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 57%
“…Moreover, cells and tumors displaying a defective HR pathway appear to be substantially more sensitive to DNA-PKcs and ATR inhibition than their HR-proficient counterparts (fig. 1) [78,80,81,86,87,88,89,92]. Future clinical trials and further preclinical experiments are required to determine the exact role that PARP, DNA-PKcs and ATR inhibitors will assume in the treatment of locally advanced and metastatic PDAC.…”
Section: Clinical Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Knittel et al () demonstrated that the allelic frequency of the TP53 mutation increased, from very low to high, in two CLL patients after fludarabine/cyclophosphamide chemotherapy, suggesting that genotoxic therapy can select this aggressive clone. We underline the importance of avoiding genotoxic therapy in patients bearing TP53 mutation, even at very low mutational load.…”
mentioning
confidence: 99%